(untitled) (Research, Society and Development, 2023)
The objective was to evaluate the religiosity of individuals hospitalized with acute coronary syndrome in an emergency hospital in Acre. This is a cross-sectional, descriptive study with a quantitative approach. The sample consisted of 65 individuals of both sexes. For data collection, the Portuguese version of the Duke religiosity scale (P-DUREL) and a form for collecting socio-demographic data were used. Most were aged between 50 and 60 years old 28 (43%), male 50 (70%), of brown race/skin color 42 (65%), with incomplete primary education 21 (32%) and the Catholic religion 33(51%). As for organizational religiosity, most demonstrated to attend church once a week 18 (28%). Faced with non-organizational religiosity, most evidenced carrying out individual religious activities 26 (40%). Regarding the intrinsic religiosity indexes, it was observed that the majority verbalized feeling the presence of God 56 (86%), that religious beliefs are really behind their whole way of living 41 (63%) and that the majority tries hard to live religion in all aspects of life 35 (54%). It is concluded that the religiosity of individuals hospitalized with acute coronary syndrome was considered satisfactory and may contribute to favorable health outcomes; however, in the present study, religion/religiosity did not influence cardiovascular risk.